An Overview Of The Pidgin And Creole - Aminah, Aminah (CV. ITTC INDONESIA, 2022)
This study wants to analyze how pidgin can use in learning a language especially in learning English. It based on creole can be a standard language while pidgin just can be developed as creole or it can be died out. It is done by looking for it origin and some theories, analyze its characteristic and how the process of the development in teaching a language especially English which has been reference of pidgin structure. There are a lot of pidgins and creoles are based on English in the making. This is a descriptive study using secondary data. The data were documents, including articles, journals and books. The data were collected through reading and reviewing documents. The data were then analyzed using a content analysis. As the result, pidgin can use in the classroom such as instruction and for a tool to learning and teaching English